THE EFFECT OF LIQUIDITY, SOLVABILITY, BINDING TIME, AND AUDITOR CHANGES ON THE AUDIT DELAY OF MANUFACTURING COMPANIES ON INDONESIA STOCK EXCHANGE LIST - Vina Putri Utami (State Islamic Institute (IAIN) Tulungagung, 2021)
This research is motivated by the importance of paying attention to audit delay in the delivery of financial reports and audit reports. This report is used for decision making, so the audit report must be submitted on time. So that the factors that can affect the audit delay need to be considered, for example liquidity, solvency, the length of the engagement, and the change of auditors. The purpose of this study is to examine the effect of the variable liquidity, solvency, length of engagement, and auditor turnover on audit delay of manufacturing companies listed on the IDX. Using this type of associative research and sampling using purposive sampling, the research shows the following results. Partially the liquidity, solvency, engagement period and auditor turnover variables have a significant effect on the audit delay of manufacturing companies listed on the IDX. Simultaneously, the variable liquidity, solvency, engagement period and auditor turnover have a significant effect on audit delay for manufacturing companies listed on the IDX.